Penfigóide bolhoso em lactente. - Beatriz Sousa; Alberto Mota; Helder Morgado; J Manuel Lopes; J Amil Dias (Acta Médica Portuguesa, 2005)
Bullous pemphigoid is an acquired auto-immune blistering disease, which affects predominantly the elderly. It is rare in children and exceptional in infant. To our knowledge only ten cases were previously reported. We report a new case of a previously healthy six months old infant who presented with erythemato-vesico-bullous cutaneous lesions over a period of six days. Histology and immunofluorescence led to the diagnosis of bullous pemphigoid. Therapy with systemic and topic corticosteroids resulted in a good outcome.